Psycho-Pedagogical Resources And The Quality Of Professional Training Of Students - Bulat, Roman; Baichorova, Hafiza (Տիգրան Մեծ)
The scientific search for intra-University potential to improve the quality of training of student is based on the improvement of the quality management system of vocational training. Further development is based not on private technical solutions, but on the reengineering of the management system aimed at activating the psychological and pedagogical resources of the University.
Keywords: Social philosophy